The Impact of Free Allophonic Variation on the Perception of Second Language Phonological Categories - Reinisch, Eva; Juhl, Katharina I.; Llompart, Miquel (Frontiers in Communication, 2020)
When learning the phonological categories of a second language (L2), learners have to deal with phonetic variation. For instance, allophonic variant forms have to be recognized as the same phoneme. A minimal pair identification task was used to assess how late Spanish learners of German perceive the phonological /r/-/h/ contrast. German /r/ was realized as one of three allophones ([r], [ʀ], [ʁ]) that vary in phonetic similarity to /h/ as well as to the typical phonetic form of Spanish /r/ (i.e., [r]). Results showed that learners were very good at identifying all German variant forms (>90% correct). However, [ʁ], which is phonetically closest to German /h/ and furthest from Spanish /r/, was identified significantly worse than [r] and [ʀ]. Relating these results to a cross-language perception task where learners were asked to map the German allophones of /r/ and the phoneme /h/ to different L1 phonological categories further showed that those learners were best at identifying words with [ʁ] who consistently matched it to a single L1 category. Surprisingly this category did not always have to be the phonologically matching Spanish [r]. We conclude that phonological and phonetic relations between the learners' L1 and L2 are important in identifying allophones of the same L2 category.